Sleep Promotion among Critically Ill Patients: Earplugs/Eye Mask versus Ocean Sound—A Randomized Controlled Trial Study - Abhilasha Chaudhary; Vinay Kumari; Neetu Neetu (Critical Care Research and Practice)
Background. Poor sleep quality is common in the intensive care unit (ICU), where several factors including environmental factors contribute to sleep deprivation. Objective. This study aims to assess and compare the effectiveness of earplugs and eye mask versus ocean sound on sleep quality among ICU patients. Design. A true experimental crossover design was used. Setting. Medical ICU of the Maharishi Markandeshwar Institute of Medical Sciences and Research Hospital, Mullana, India. Participants. Sixty-eight patients admitted in the medical ICU were randomly allocated by lottery methods into group 1 and group 2. Methods. Nocturnal nine-hour (10 : 00 pm to 7 : 00 am) for a four-night period were measured. Earplugs and eye mask versus ocean sound were crossed over between two groups. Subjective sleep quality of four nights was assessed using a structured sleep quality scale. Scores for each question range from 0 to 3, with a higher score indicating poor sleep quality. Results. Repeated measures ANOVA showed that there was a significant change in the sleep quality score (p=0.001), which showed that sleep quality score was improved after the administration of earplugs and eye mask and ocean sound. Fisher’s LSD post hoc comparison showed a significant difference (p=0.001). Conclusion. Earplugs and eye mask were better than ocean sound in improving sleep quality. Earplugs, eye mask, and ocean sound are safe and cost effective, which could be used as an adjuvant to pharmacological interventions to improve sleep quality among ICU patients. However, further research in this area needs to be conducted. This trial is registered with NCT03215212.